2022
DOI: 10.1088/1674-4527/aca233
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the Main Phases of the Super Geomagnetic Storms (ΔSYM-H ≤ −250 nT) with Different Heliolongitudes

Abstract: We studied the properties of the main phases of 24 super geomagnetic storms (SGSs) (ΔSYM-H ≤ −250 nT) since 1981. We divided the SGSs into two subgroups: SGSs-I ( −400 nT< ΔSYM-H ≤ −250 nT) and SGSs-II (ΔSYM-H ≤ −400 nT). Of the 24 SGSs, 16 are SGSs-I and 8 are SGSs-II. The source locations of SGSs were distributed in the longitudinal scope of [E37, W66]. 95.8% of the SGSs were distributed in the longitudinal scope of [E37, W20]. East and west hemispheres of the Sun had 14 and 10 SGSs, respectively. The dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…However, the enhanced R-M effect described by the enhanced by the ring current effect influenced by the solar wind dynamic pressure has not been reported. It has been found that the ring current effect caused by the solar wind during a period should be indicated by ∆SYM-H rather than by the minimum of the SYM-H index (Zhao, Le, and Liu, 2023).…”
Section: Discussion and Summarymentioning
confidence: 99%
“…However, the enhanced R-M effect described by the enhanced by the ring current effect influenced by the solar wind dynamic pressure has not been reported. It has been found that the ring current effect caused by the solar wind during a period should be indicated by ∆SYM-H rather than by the minimum of the SYM-H index (Zhao, Le, and Liu, 2023).…”
Section: Discussion and Summarymentioning
confidence: 99%